Sosialisasi Konsep Pertanian Berkelanjutan Di Kampung Napua Distrik Napua Kabupaten Jayawijaya - Herlyani S; Futri Wulandari (Pakis Journal Institute, 2024)
Traditional agriculture implemented in Napua Village, Napua, Jayawijaya indirectly has a negative impact on the environment and the sustainability of food production. Socialization and assistance regarding the concept of sustainable agriculture is important to increase farmers' awareness in implementing more environmentally friendly and sustainable agricultural practices. This service activity aims to provide farmers with an understanding of the concept of sustainable agriculture. The implementation method is socialization in the form of delivering material about sustainable agriculture and assistance to farmer groups in practicing the concept of sustainable agriculture. The results of this socialization activity are the emergence of farmer awareness about the factors causing the decline in the quality and quantity of agricultural products in Napua Village and increased knowledge about the concept of sustainable agriculture as a solution to the problems.